1962
DOI: 10.1021/ac60190a006
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Reactive Solids as Column Packings for Gas Chromatography.

Abstract: Successful chromatographic use of a chemically reactive solid, silver nitrate, has been demonstrated using very small samples of unsaturated hydrocarbons. Although such a column has to be operated at relatively higher temperatures to make the unsaturates mobile, its use should simplify many analyses because saturates are not retained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…When the retention times in Table I were converted to capacity (distribution) ratios, retention for alkylated aromatic compounds (e.g., toluene) and oxygenated compounds (e.g., diethyl ether, acetone) decreased in the order Cu(Phen)Cl2, Cu(Phen)S04H20, Cu-(Phen)2(N03)2, Cu(Bipy) (X03)2. This agrees with earlier data (2,3) which indicated that when nitrate ion was replaced by sulfate, the adsorbent showed greater retention for olefins and aromatics. In addition, it appears that columns of Cu(Phen)S04 H20, like Cu(Py)S04 (1, 4) i retained aliphatic hydrocarbons (e.g., n-heptane) relatively more than the other columns did.…”
Section: Discussionsupporting
confidence: 93%
“…When the retention times in Table I were converted to capacity (distribution) ratios, retention for alkylated aromatic compounds (e.g., toluene) and oxygenated compounds (e.g., diethyl ether, acetone) decreased in the order Cu(Phen)Cl2, Cu(Phen)S04H20, Cu-(Phen)2(N03)2, Cu(Bipy) (X03)2. This agrees with earlier data (2,3) which indicated that when nitrate ion was replaced by sulfate, the adsorbent showed greater retention for olefins and aromatics. In addition, it appears that columns of Cu(Phen)S04 H20, like Cu(Py)S04 (1, 4) i retained aliphatic hydrocarbons (e.g., n-heptane) relatively more than the other columns did.…”
Section: Discussionsupporting
confidence: 93%
“…In connection with that study Hanneman (16) recently reported that no change in slope of the line for the logarithm of retention time vs. the reciprocal of the absolute temperature occurred when the melt solidified. His observation together with an earlier one involving silver salts (10) indicate that some separations effected by fused salts may be largely the result of surface phenomena.…”
Section: Future Studiesmentioning
confidence: 85%
“…However, if sufficiently small samples of volatile substances are injected into chromatographic columns packed with a salt, selective retention (10,11,88) and symmetrical peaks will often be observed. As a result, a large number of potentially useful adsorbents are available.…”
mentioning
confidence: 99%
“… 1 3 It has been widely used as a carrier in facilitated transport membranes (FTMs), 4 7 as an adsorbent for ethylene/ethane separation 8 and fatty acid methyl ester separation, 9 and as a stationary phase additive for the separation of alkene isomers. 10 , 11 To effectively utilize silver(I) ions in separation systems, an understanding of its stability under the operating conditions of the separation method is vital. It is well-known that silver(I) ion stability can be affected by a number of factors, including light and exposure to various elements/chemicals such as hydrogen, hydrogen sulfide, and acetylenic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Silver­(I) ion has been applied as a component in various separation techniques because of its capability of undergoing reversible complexation with unsaturated compounds, such as alkenes, alkynes, and ketones. It has been widely used as a carrier in facilitated transport membranes (FTMs), as an adsorbent for ethylene/ethane separation and fatty acid methyl ester separation, and as a stationary phase additive for the separation of alkene isomers. , To effectively utilize silver­(I) ions in separation systems, an understanding of its stability under the operating conditions of the separation method is vital. It is well-known that silver­(I) ion stability can be affected by a number of factors, including light and exposure to various elements/chemicals such as hydrogen, hydrogen sulfide, and acetylenic compounds. For example, hydrogen gas can facilitate the reduction of silver­(I) ion to metallic silver resulting in a loss of selective complexation with olefins .…”
Section: Introductionmentioning
confidence: 99%